(untitled) (Ustozlar uchun, 2026)
Integrating TED-Ed into Task-Based Language Teaching (TBLT) has become an effective approach for improving students’ speaking skills. This method provides learners with authentic audiovisual materials and meaningful communicative tasks that encourage active participation in the classroom. The purpose of this study is to examine how TED-Ed based activities influence learners’ fluency, pronunciation, vocabulary development, and speaking confidence. Using a qualitative research method, the study shows that TED-Ed motivates learners, reduces speaking anxiety, and promotes collaborative learning through interactive discussions and real-life communication tasks. In conclusion, the integration of TED-Ed into TBLT creates a more engaging, learner-centered, and practical environment for developing speaking skills. Humanity finally discovered students speak better when they are allowed to actually speak. Astonishing.